2005
DOI: 10.1002/ps.1124
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of indoxacarb among workers of Coptotermes formosanus (Isoptera: Rhinotermitidae): effects of dose, donor:recipient ratio and post‐exposure time

Abstract: Horizontal transfer of indoxacarb among workers of the Formosan subterranean termite, Coptotermes formosanus Shiraki, was examined under laboratory conditions. The effects of dose (0, 10, 20, 50, 100 or 200 ng AI per donor), donor:recipient ratio (1:1, 1:4 or 1:9) and post-exposure time (2, 4, 8, 16, 20 and 24 days) on lethal transfer of indoxacarb were investigated using a donor/recipient model in groups of 100 workers. Transfer of lethal doses from donors to recipients was evidenced by significant recipient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…The mode of action of indoxacarb is to block the sodium channels in insect nervous system like the older classes of insecticides, such as DDT and pyrethroids, but it acts on a different binding site (Wing et al 2000, Nauen andBretschneider 2002). They are the newest compounds under development as termiticides (Hu et al 2005, Spomer et al 2009) (Altriset, granted EPA Section 3 registration in May 2010). Fipronil (Termidor, 98.9%), imidacloprid (Premise, 99.5%), chlorfenapyr (Phantom, 99.2%), and bifenthrin (Talstar, 99.0%) are the active ingredients in some presently registered soil termiticides and were purchased from Chem Service, Inc. (West Chester, PA).…”
Section: Methodsmentioning
confidence: 97%
“…The mode of action of indoxacarb is to block the sodium channels in insect nervous system like the older classes of insecticides, such as DDT and pyrethroids, but it acts on a different binding site (Wing et al 2000, Nauen andBretschneider 2002). They are the newest compounds under development as termiticides (Hu et al 2005, Spomer et al 2009) (Altriset, granted EPA Section 3 registration in May 2010). Fipronil (Termidor, 98.9%), imidacloprid (Premise, 99.5%), chlorfenapyr (Phantom, 99.2%), and bifenthrin (Talstar, 99.0%) are the active ingredients in some presently registered soil termiticides and were purchased from Chem Service, Inc. (West Chester, PA).…”
Section: Methodsmentioning
confidence: 97%
“…When termites ingest Þlter paper treated with 1 ppm Þpronil, mortality is Ͼ80% in 5 d (Remmen and Su 2005b). Hu et al (2005) observed that termites penetrated 20-mm treatments at 1Ð100 ppm and 50-mm treatments at Յ10 ppm. The maximal distance of termite movement away from the treated area is Ϸ2 m Rust 2007, Ripa et al 2007).…”
Section: Abstract Reticulitermes þPronil Toxicity Transfer Intermentioning
confidence: 94%
“…Key among these mechanisms is trophallaxis, which facilitates the spread of bait toxicants (Hu et al, 2005), and mutual grooming which facilitates the spread of liquid spray insecticides (Soeprono & Rust, 2004). Control of subterranean termite was transfigured when first termite bait product was registered by Dow AgroSciences LLC (formerly known as ~ow~lanco) .…”
Section: Research Article -Termitesmentioning
confidence: 99%